INCIDENCE OF CATTLE MYIASIS IN CENTRAL IRAQ - R. Ali, S. (The Iraqi Journal of Veterinary Medicine, 1988)
Through a full calander year a total of 2220 (1089 male and 1131 female) cattle were examined for Hypoderma spp. No difference was noticed in infestation rates of the two sexes. Larvae found on the back region of the animals during late Autumn and Winter months with the peak rate of infestation (25.2%) in February. While, amongst the months with positive cases, April and November showed the lower rates 3.1% and 3.4% respectively.